Protocol for 3D virtual histology of unstained human brain tissue using synchrotron radiation phase-contrast microtomography - Lee, Ju Young; Donato, Sandro; Mack, Andreas F.; Mattheus, Ulrich; Tromba, Giuliana; Longo, Elena; D’Amico, Lorenzo; Mueller, Sebastian; Shiozawa, Thomas; Bause, Jonas; Scheffler, Klaus; Longo, Renata; et al. (Frontiers in Physics, 2024)
X-ray phase-contrast micro computed tomography using synchrotron radiation (SR PhC-µCT) offers unique 3D imaging capabilities for visualizing microstructure of the human brain. Its applicability for unstained soft tissue is an area of active research. Acquiring images from a tissue block without needing to section it into thin slices, as required in routine histology, allows for investigating the microstructure in its natural 3D space. This paper presents a detailed step-by-step guideline for imaging unstained human brain tissue at resolutions of a few micrometers with SR PhC-µCT implemented at SYRMEP, the hard X-ray imaging beamline of Elettra, the Italian synchrotron facility. We present examples of how blood vessels and neurons appear in the images acquired with isotropic 5 μm and 1 µm voxel sizes. Furthermore, the proposed protocol can be used to investigate important biological substrates such as neuromelanin or corpora amylacea. Their spatial distribution can be studied using specifically tailored segmentation tools that are validated by classical histology methods. In conclusion, SR PhC-µCT using the proposed protocols, including data acquisition and image processing, offers viable means of obtaining information about the anatomy of the human brain at the cellular level in 3D.